Health-related Internet Use Among New Urology Clinic Patients - Zhu, Michael; Patel, Rutul D.; Dave, Priya; Ohmann, Erin; Laudano, Melissa; Lowe, Franklin; Donnelly, Jillian; Maria, Pedro; Sankin, Alex; Small, Alexander C.; Watts, Kara L. (Urology (Ridgewood, N.J.), 2024)
To assess internet usage among new patients seen by urologists and impact on post-consultation understanding for 4 common conditions: kidney stones, elevated prostate-specific antigen, male voiding, and female voiding. We performed a prospective study of new urology patients at our diverse urban, academic urology practice for the above conditions over a 1-year period. A voluntary questionnaire assessed patients’ internet use related to referred conditions prior to encounters. Questions evaluated quality of information and patient understanding of symptoms/condition at baseline, after online searches, and after their urology visit. A patient-reported Likert scale of 1 (poor) to 10 (excellent) was used and internet “searchers” were compared to “non-searchers.” Two hundred fifteen patients participated. Most respondents were Latino (41%) or Black (35%) and English-speaking (81%). Cohorts comprised 130 searchers (60%) and 85 non-searchers (40%). Searchers were significantly younger (median 53 vs 63 years, P <.001), more likely to have home internet access (P <.001), and more general medical internet use (P <.001). Overall, patients’ understanding of visit diagnoses increased after their encounters (median pre-visit rating 5 vs post-visit rating 10). Searchers reported a greater post-visit understanding compared to non-searchers (median rating 10 vs 9, P <.001), and a greater change in understanding from baseline (median +4 vs +3, P = .02). Internet use is common amongst younger patients referred to urologists and may be associated with improved understanding of their condition after urologic consultation. Continued investigation of patient uses and attitude towards popular online resources can help urologists curate resources to benefit patients and providers alike.